Expression of the ZNT1 Zinc Transporter from the Metal Hyperaccumulator Noccaea caerulescens Confers Enhanced Zinc and Cadmium Tolerance and Accumulation to Arabidopsis thaliana - Lin, Ya-Fen (PLoS One, 2016)
Prompt regulation of transition metal transporters is crucial for plant zinc homeostasis. NcZNT1 is one of such transporters, found in the metal hyperaccumulator Brassicaceae species Noccaea caerulescens. It is orthologous to AtZIP4 from Arabidopsis thaliana, an important actor in Zn homeostasis. We examined if the NcZNT1 function contributes to the metal hyperaccumulation of N. caerulescens. NcZNT1 was found to be a plasma-membrane located metal transporter. Constitutive overexpression of NcZNT1 in A. thaliana conferred enhanced tolerance to exposure to excess Zn and Cd supply, as well as increased accumulation of Zn and Cd and induction of the Fe deficiency response, when compared to non-transformed wild-type plants. Promoters of both genes were induced by Zn deficiency in roots and shoots of A. thaliana. In A. thaliana, the AtZIP4 and NcZNT1 promoters were mainly active in cortex, endodermis and pericycle cells under Zn deficient conditions. In N. caerulescens, the promoters were active in the same tissues, though the activity of the NcZNT1 promoter was higher and not limited to Zn deficient conditions. Common cis elements were identified in both promoters by 5’ deletion analysis. These correspond to the previously determined Zinc Deficiency Responsive Elements found in A. thaliana to interact with two redundantly acting transcription factors, bZIP19 and bZIP23, controlling the Zn deficiency response. In conclusion, these results suggest that NcZNT1 is an important factor in contributing to Zn and Cd hyperaccumulation in N. caerulescens. Differences in cis- and trans-regulators are likely to account for the differences in expression between A. thaliana and N. caerulescens. The high, constitutive NcZNT1 expression in the stele of N. caerulescens roots implicates its involvement in long distance root-to-shoot metal transport by maintaining a Zn/Cd influx into cells responsible for xylem loading.